Primary gastric Hodgkin's lymphoma: favourable outcome following multi-agent chemotherapy without surgical intervention. (15th February 2011) - Quintyne, KI; Mulcahy, E; Wallis, F; Wilson, L; Gupta, RK
Abstract : The authors report the case of a 51-year-old man who presented with left-sided abdominal pain and weight loss associated with drenching night sweats. Preliminary blood tests yielded no specific cause for his symptoms, but abdominal ultrasound revealed multiple hepatic lesions and peripancreatic lymphadenopathy. Further imaging, including positron emission tomography (PET)/CT, revealed fludeoxyglucose 18F (FDG) avid uptake within lymphadenopathy above and below the diaphragm and also noted gastric thickening. Diagnosis was established with gastric biopsy and revealed gastric Hodgkin's lymphoma. He was started on and tolerated multi-agent chemotherapy. Repeated PET/CT and gastric biopsy showed complete metabolic and pathologic response to treatment.